Mesenchymal stem cells inhibit proliferation of lymphoid origin haematopoietic tumour cells by inducing cell cycle arrest - Sarmadi, Vahid Hosseinpour; Tong, Chih Kong; Vidyadaran, Sharmili; Abdullah, Maha; Seow, Heng Fong; Ramasamy, Rajesh (Malaysian Medical Association, 2010)
We have previously shown that mesenchymal stem cells (MSC) inhibit tumour cell proliferation, thus promising a novel therapy for treating cancers. In this study, MSC were generated from human bone marrow samples and characterised based on standard immunophenotyping. When MSC were co-cultured with BV173 and Jurkat tumour cells, the proliferation of tumour cells were profoundly inhibited in a dose dependent manner mainly via cell to cell contact interaction. Further cell cycle analysis reveals that MSC arrest tumour cell proliferation in G0/G1 phase of cell cycle thus preventing the entry of tumour cells into S phase of cell cycle.